2022
DOI: 10.1186/s41235-022-00365-x
|View full text |Cite
|
Sign up to set email alerts
|

The interactive functional biases of manual, language and attention systems

Abstract: Hemispheric lateralisation is a fundamental principle of functional brain organisation. We studied two core cognitive functions—language and visuospatial attention—that typically lateralise in opposite cerebral hemispheres. In this work, we tested both left- and right-handed participants on lexical decision-making as well as on symmetry detection by means of a visual half-field paradigm with various target–distractor combinations simultaneously presented to opposite visual fields. Laterality indexes were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…The lateralization of individual functions, such as language, may be closely associated with the lateralization of many seemingly independent processes 43 . Several studies suggest that the LH specialization for language may be linked to the concept of “complementary lateralization.” This stands in contrast to the preferential specialization of the contralateral hemisphere (the RH) for other high-level cognitive functions like visuospatial processing 6771 . It has also been reported that the absence of functional lateralization for language production reduces performance in language tasks and other non-verbal, high-level functions 72 .…”
Section: Discussionmentioning
confidence: 67%
“…The lateralization of individual functions, such as language, may be closely associated with the lateralization of many seemingly independent processes 43 . Several studies suggest that the LH specialization for language may be linked to the concept of “complementary lateralization.” This stands in contrast to the preferential specialization of the contralateral hemisphere (the RH) for other high-level cognitive functions like visuospatial processing 6771 . It has also been reported that the absence of functional lateralization for language production reduces performance in language tasks and other non-verbal, high-level functions 72 .…”
Section: Discussionmentioning
confidence: 67%
“…This is further supported by data from individuals with agenesis of the corpus callosum who show an increased distribution of language processing across hemispheres in addition to right-hemispheric dominance (Hinkley et al, 2016). The left-sided superiority such as for the ability to recognise written words or to extract meaning has been demonstrated in neuroimaging work (Price, 2000;Josse and Tzourio-Mazoyer, 2004), and behavioural research that has revealed performance advantages when words are presented to the right as compared to left visual field (Hunter and Brysbaert, 2008;Serrien and O'Regan, 2022). Two influential models are proposed in the literature to explain these lateralised effects.…”
Section: Introductionmentioning
confidence: 76%
“…Two additional language-related variants have been confirmed through neuroimaging work: no hemispheric dominance with bilateral representations, a pattern that is rather equally present in both handedness groups, in addition to right-hemispheric dominance that is usually only observed in a small subgroup of lefthanders (Tzourio-Mazoyer et al, 2016;Vingerhoets, 2019). Taking these differences into account, it is therefore relevant to consider the profiles that characterise their behaviour (Serrien and O'Regan, 2022). Our data revealed that the participants from both handedness groups had distinct sensitivity during intra-and interhemispheric conditions.…”
Section: Individual Handedness-language and Complementary Intra-inter...mentioning
confidence: 92%
See 2 more Smart Citations